Epigenetic Therapeutics: A New Weapon in the War Against Cancer - Ahuja, Nita (Annu Rev Med, 2016)
The past 15 years have seen an explosion of discoveries related to the cellular regulation of phenotypes through epigenetic mechanisms. This regulation provides a software that packages DNA, without changing the primary base sequence, to establish heritable patterns of gene expression. In cancer, many aspects of the epigenome, controlled by DNA methylation, chromatin, and nucleosome positioning, are altered as one means by which tumor cells maintain abnormal states of self-renewal at the expense of normal maturation. Epigenetic and genetic abnormalities thus collaborate in cancer initiation and progression, as exemplified by frequent mutations in genes encoding proteins that control the epigenome. There is growing emphasis on using epigenetic therapies to reprogram neoplastic cells toward a normal state. Many agents targeting epigenetic regulation are under development and entering clinical trials. This review highlights the promise that epigenetic therapy, often in combination with other therapies, will become a potent tool for cancer management over the next decade.